(untitled) (Journal of Science and Technology, 2016)
In order to observe the morphological changes that occur in cell-cell and cell-matrix interactions among trophoblast cells and other neighbouring cells during human implantation, BeWo cells were cultured in a 3-dimensional artificial extracellular matrix (Matrigel) using a double-chamber system. These cultures were then processed for light and electron microscopical examination. Results obtained show that the morphology and behavioural pattern of BeWo cells grown on Matrigel is similar to that reported for in vitro normal human cytotrophoblast cells on extracellular matrix (ECM). These results suggest that culture of BeWo cells on extracellular matrices may be useful for the study of some of the early embryonic events leading to human implantation, especially during the period when trophoblastic cells interact with and erode the uterine epithelium and ECM.